Aplicación del modelo de Peleg en la deshidratación osmótica al vacío de Smallanthus sonchifolius. - Oblitas, J. (2022)
The applicability of Peleg model to predict mass transfer kinetics during the osmotic dehydration (OD) process of yacon was investigated by using 3 different concentrations of sucrose solution, 3 vacuum pressures, 3 temperatures and 9 times. When analyzing the effect on solids gain, it shows a linear effect over time, while the other parameters show quadratic effects. Similarly, the loss of water continues to have a linear trend as a function of time, while for the other parameters there is a decreasing behavior as temperature, concentration and pressure increase. The equilibrium values predicted by the Peleg equation were very close to the experimental ones, with values of R2>0.98. Regarding the Peleg's rate constants, the results showed that that K1 was significantly (p<0.05) affected as the concentration of … and the temperature were increased. With regard to K2, this constant was significantly affected (p<0.05) by increasing the values of the three studied parameters, probably due to the phenomena of cellular relation because of the effect of pressure with the consequent increase of the volume.